2014
DOI: 10.1073/pnas.1411267111
|View full text |Cite
|
Sign up to set email alerts
|

Ancient translation factor is essential for tRNA-dependent cysteine biosynthesis in methanogenic archaea

Abstract: Significance Translation requires aminoacyl-tRNAs that are mainly formed by acylating tRNAs with the corresponding amino acids. Methanogenic archaea synthesize Cys-tRNA in an unusual indirect fashion. They attach a precursor amino acid, phosphoserine, to tRNA Cys , which is then converted to cysteine. This study shows that the indirect Cys-tRNA formation is carried out in a multienzyme complex assembled by a translation factor. Complex formation markedly promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Cys ) is essential for Cys-tRNA formation in methanogens (38). It is likely that the tRNA-dependent selenocysteine pathway also may involve a complex of tRNA Sec , SerRS, PSTK, and SepSecS (39).…”
Section: Sepcyse and Trnamentioning
confidence: 99%
“…Cys ) is essential for Cys-tRNA formation in methanogens (38). It is likely that the tRNA-dependent selenocysteine pathway also may involve a complex of tRNA Sec , SerRS, PSTK, and SepSecS (39).…”
Section: Sepcyse and Trnamentioning
confidence: 99%
“…The initial Ser residue present in the Ser-tRNA [Ser]Sec is phosphorylated by PSTK, resulting in an intermediate ophosposeryl-(Sep)-tRNA [Sep]Sec . Following the conversion, the o-phosphoseryl-tRNA Sec selenium transferase (SepSecS-a PLPdependent enzyme) performs the Sep/Sec conversion, resulting in the mature Sec-tRNA Sec (Liu et al, 2014). The biological selenium compound is delivered as mentioned for bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This system also acts as the sole route for cysteine biosynthesis for these organisms 8 . More recently, it was reported that a third protein SepCysE (SepRS/SepCysS pathway enhancer) is necessary for coupling the consecutive two reactions and for enhancing tRNA Cys binding 11 . Thus, the SepRS, SepCysE, and SepCysS ternary complex (named the transsulfursome) is responsible for the whole process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the SepRS, SepCysE, and SepCysS ternary complex (named the transsulfursome) is responsible for the whole process. SepCysE is preserved in class I methanogens, which evolved before other methanogens and may have appeared as the ancestral Euryarchaeota 11 , 12 . Therefore, elucidation of the functional mechanism of this system is of vital importance as it may explain the mechanism by which cysteine was added to the genetic code.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation